Anders Melin, Living with Other Beings: A Virtue-Oriented Approach to the Ethics of Species Protection - Milligan, Anthony (Journal for the Study of Religion, Nature and Culture, 2018)
Anders Melin, Living with Other Beings: A Virtue-Oriented Approach to the Ethics of Species Protection (Studies in Religion and the Environment; Berlin: LIT Verlag, 2013), 184pp., 44.95, ISBN: 978-3643904201.